O efeito do ensino de relações de equivalência sobre o comportamento de culpabilizar vítimas de estupro - Freitas, Júlia Castro de Carvalho (2019)
In our society, rape is usually seen as an act that a strange man uses physical force to sexually assault a woman who clearly resists to his moves. This conventional view implies that people only label as “rape” a situation that matches this description, although it doesn’t cover the diversity of circumstances and behaviors found among rapes. Especially when a rape situation doesn’t fit into the stereotype, the rape victim is commonly blamed for this act. From the stimulus equivalence paradigm viewpoint, it can be said that the rape victim and the concept of responsible are part of the same equivalence class. Many studies have been done since the 1990’s aiming to reverse socially relevant equivalence classes and had unsatisfactory results. However, an experiment conducted by Mizael et al. (2016) reached positive results on the racial biased pre-experimental classes reversion. The present study used a similar method and had the goal of investigating the effect of teaching new stimulus classes on the rape victim blame behavior. The participants responded to three instruments in pre and post-test phases: an attribution of responsibility scale, a rape myth acceptance scale, and the IRAP. These instruments aimed to identify biases related to people and circumstances involved in rapes. The results showed that the training produced the formation of the new equivalence classes in the majority of participants, which means a modification in the pre-experimental classes. This change affected self-report instruments, but not on IRAP. Differences between the results of the two kinds of measure can be explained by contextual control.